THE ARIZONA WATER-ENERGY NEXUS: ELECTRICITY FOR WATER AND WASTEWATER SERVICES - Hoover, Joseph Hamilton (The University of Arizona., 2009)
The water-energy nexus is the dependent relationship between water and energy resources. The nexus results in complex policy and management challenges for resources that have been historically managed independently. This study quantifies electricity used for water service provision in Arizona. Employing the water use cycle as an analysis tool, this study divides municipal water use for the Tucson metropolitan area and city of Phoenix into four components. The findings suggest that energy intensity differences between Phoenix and Tucson exists due to geographic variables. The city of Phoenix and Tucson metropolitan area currently consume 1.2% of statewide electricity for water and wastewater service. Electricity demand for water and wastewater service in Tucson for 2008-2030 will be 110-131%, which is greater than the 85% electricity growth statewide. Water and wastewater agencies now face decisions regarding future plans to meet water demand and maintain a low overall energy use for service provision.